Analysis of Effect of Work Motivation and Job Satisfaction Performance Against Serdang Agricultural Extension Bedagai - Risa Kartika Lubis (Institute of Computer Science (IOCS), 2020)
This study was conducted to Determine Whether there is a positive and significant influence between work motivation and job satisfaction both partially and simultaneously on the performance of agricultural instructors in Bedagai Serdang district. The population in this study were all agricultural extension workers, amounting to 110 in the BP2KP district of Serdang Bedagai. This study took all Populations as a sample (census). Data collection instruments using a questionnaire technique. Analyzed data Came from distributing questionnaires to employees who were sampled in this study with a Likert scale measurement. Hypothesis analysis is done by multiple linear regression analysis with the SPSS 22 software program. The results of hypothesis testing show that (1) work motivation has a positive and significant effect on the performance of agricultural instructors. (2) job satisfaction has a positive and significant effect on the performance of agricultural instructors (3) simultaneously work motivation and job satisfaction have a positive and significant effect on the performance of agricultural instructors.